Efeitos do treinamento de for??a com diferentes volumes sobre a atividade das metaloproteinases do tipo 2 e 9 na circula????o, m??sculo esquel??tico e tecido adiposo de ratos - Sousa Neto, Ivo Vieira de (2017)
Matrix metalloproteinases (MMPs) play an important physiological role in tissue remodeling. However, the effect of resistance training (RT) volume on MMP activity in different tissues and serum remains to be determined. Thus, the aim of the present study was to investigate the effects of different RT volume on MMP activity in skeletal muscle, visceral adipose tissue and in the circulation. Twenty-one four-month-old Wistar rats were randomly divided into three groups (n=7 per group): sedentary control (SC); RT with four ladder climbs (RT-4; 50%, 75%, 90% and 100% of their maximal carrying capacity) and TR with eight ladder climbs (RT-8 with two sets for each load). The eightweek RT consisted of climbing a 1.1-m vertical ladder with weights secured to the animals??? tails. MMP-2 and -9 activity were analyzed by zymography. RT-8 group displayed higher active MMP-2 activity as compared with SC and RT-4 in skeletal muscle (p < 0.05). There was no significant difference between groups for pro-MMP-2 and intermediate-MMP-2 activity in visceral adipose tissue, while RT-8 group presented lower active MMP-2 activity as compared with SC (p < 0.05). Plasma pro and active MMP-2 and MMP-9 activity was lower in RT-8 as compared with RT-4 (p < 0.05). These results suggest that higher volume RT is able to positively modulate the activity of MMPs in skeletal muscle (up-regulating), visceral adipose tissue and circulation (downregulating). These effects are important for the physiological and homeostatic functions of tissues.